'Everyone needs a Willie': The elusive position of deputy to the British prime minister. Issue 4 (November 2017) - Kirkup, Jonathan; Thornton, Stephen
Abstract This article examines the post of deputy to the UK prime minster, an office officially 'unknown to the constitution'. Employing a largely chronological approach, the article has two key objectives: to establish who and under what terms an individual might be considered a deputy to the prime minister – a list that is more expansive than those traditionally identified as 'deputy prime minister'; to categorise these individuals to create a basic typology. Though more research will be required to substantiate the claim, a further argument tentatively made here is that, although the position of deputy remains constitutionally invisible, the office's roles and responsibilities have become an increasingly important part of the management of the core executive and effective government. Overall, in a constitution already famous for its slippery qualities, this article will demonstrate that the position of deputy to the British prime minister is particularly lubricious.